Methyl 1-(7-acetamido-5,8-dimethoxyquinolin-2-yl)-4-methyl-β-carboline-3-carboxylate - Felix Nissen (Acta Crystallographica Section E, 2011)
The title compound, C27H24N4O5, is an intermediate in the synthesis of lavendamycin via a ruthenium-catalysed [2 + 2 + 2] cycloaddition. An intramolecular hydrogen-bond bridge from the carboline to the quinoline stabilizes a highly planar geometry [maximum deviation = 0.065 (6) Å] for the two rigid units. This hydrogen-bond-stabilized coplanarity has a very close analogy in the structure of the antitumor antibiotic streptonigrin in the solid state and in solution. Intermolecular hydrogen-bond bridges of amides groups along the a axis and π–π stacking interactions [centroid–centroid distance = 3.665 (9) Å] connect molecules arranged in a parallel manner.